Infrastructure Facilities, Awareness, and Consumer Purchasing Behaviour in Organized Retail Stores - feedback of Dairy and Food Consumers of in Anand City - Dhruvi R. Solanki; M.C. Prajapati; A.K. Makwana; M.D. Gurjar; K.C. Kamani (Archives of Current Research International, 2025)
This research investigates the infrastructure quality, consumer awareness, and purchasing behaviour across retail stores in Anand and Vidyanagar, Gujarat. The study evaluates nine prominent retail outlets, including supermarkets, hypermarkets, and convenience stores, with a particular focus on the Amul Green Retail Store. Using a structured questionnaire and direct observation, data were collected from 100 consumers and through in-store assessments. Findings reveal that large-format retailers like D-Mart and Smart Bazaar outperform others in terms of infrastructure, product variety, and customer amenities such as billing counters, parking, and washroom facilities. Amul Green, although offering a moderate range of essential products, lacks key infrastructure elements and brand visibility—only 49% of respondents were aware of its existence, and 52% reported never shopping there. Consumer demographic analysis indicated a predominantly young (86% aged 18–26), urban (81%), and educated sample with strong purchasing power. Purchase behaviour trends showed a clear preference for D-Mart and Sardar Ganj Market, driven by convenience and pricing. The study concludes that to remain competitive, smaller retailers must upgrade infrastructure, improve customer experience, and strengthen marketing efforts. The research offers insights valuable for retail strategists and policymakers aiming to optimize consumer engagement and retail performance in semi-urban Indian markets.